APPLICATION DEVELOPMENT "MY BESTIE KESPRO" AS AN ANDROID-BASED ADOLESCENT REPRODUCTIVE HEALTH EDUCATION MEDIA - Muhlisa1, Ridwan Amiruddin2, Apik Indarty Moedjiono3, Suriah4, Rizal Damanik5, Ummu Salmah6, Sudirman Nasir7, Intan Sari Areni8, (Chelonian Research Foundation, 2024)
Introduction: Media is one of the means of learning for adolescents. Media use in health education can help clarify information with an attractive display that is easily accessible and operated and involves the five senses. The current era of digitalisation encourages public health literacy to increase, especially in adolescents close to gadgets, so it is known as e-health literacy. Namely, digital health literacy is the ability to search, find, and understand health information available in electronic resources and use information obtained from these resources to overcome health problems. Objectives: To develop the My Bestie Kespro application as a medium for promoting reproductive health. Method: This type of research is qualitative with an exploratory case study approach. Research Results: The results of the expert review of the My Bestie Kespro application found that the average score based on the design was 4.66, with suitable criteria. The results of the end user trial are > 80% (reaching 90%) with perfect and reasonable criteria. Conclusion: My Bestie Kespro application media is suitable to be used as a medium for reproductive health education in adolescents. Keywords: Media, My Bestie Kespro, Reproductive Health, Application